Observation of peroxynitrite overproduction in cells during 5-fluorouracil treatment via a ratiometric fluorescent probe. Issue 18 (5th February 2020) - Hou, Ji-Ting; Wang, Bingya; Zhang, Yongru; Cui, Beibei; Cao, Xinhua; Zhang, Man; Ye, Yong; Wang, Shan
Abstract : A ratiometric fluorescent probe was described for imaging the production of peroxynitrite in cells stimulated by 5-FU. Abstract : We describe a colorimetric and fluorescent probe 3a to detect cellular peroxynitrite with high selectivity and sensitivity. 3a was successfully applied in the bioimaging of exogenous and endogenous peroxynitrite in living cells. The up-regulation of peroxynitrite in cancer cells and normal cells during 5-fluorouracil treatment was finally monitored.